Desenvolvimento de nova fase extratora para amostragem passiva de agrotóxicos em águas com determinação por GCxGC/Q-TOFMS/MS - Nayara Silva Fraga (2023)
Pesticides are a class of compounds widely used, especially in agricultural countries, such as Brazil, in the fight against pests such as fungi, insects, bacteria, herbs, rodents, among others. The exacerbated consumption of these products alerts the scientific community to its potential danger to human health, water, soil, animals, that is, the environment. Thus, it is important to provide the study of techniques that are efficient in the extraction and identification of these pollutants in environmental matrices, as well as their monitoring for regulatory purposes. The present work proposed the development of a method for passive sampling of 23 pesticides in surface waters. The extraction method used was based on the use of polydimethylsiloxane polymer as sorbent, filling a polypropylene fiber. The polydimethylsiloxane fiber prepared in this study was characterized by thermal analysis, infrared spectroscopy with Fourier transform and scanning electron microscopy. The extraction process was optimized in terms of the choice of solvent extractor, evaluating the influences of the factors: extraction time, agitation during extraction, desorption time, desorption temperature and stirring time in vortex. The solvent chosen was ethyl acetate and the factors studied showed no statistically significant influence for the experimental domain considered. The selected conditions were 30 min of extraction, agitation at 400 rpm, 5 min of desorption at 65 ºC and 1 min of agitation in the vortex. For the calibration process of the proposed sampling system was conducted a previous study of degradation kinetics, which resulted in stabilization of concentrations in a period of 10 days for most pesticides of interest. For the optimized extraction method were evaluated some figures of merit. The variances were explained with levels above 92.0 %; the limits of quantification ranged between 0,0011 and 33,30 μg L-¹; repeatability and intermediate accuracy were below 20,0 %; and recoveries were between 80,20 and 119,7 %. The proposed method of extraction and analysis of pesticides is promising for application in passive sampling due to the stability of the polymeric material extractor, the possibility of modification of its chemical affinity by incorporation to other polymeric materials and/or nanomaterials, the easy construction of the sampling device, as well as the sensitivity and selectivity offered by the GCxGC/QTOFMS/MS technique.